Advances in water power-control hydraulics experimental research - Majdič, Franc (Strojniški vestnik, 2008)
Environmental protection regulations are becoming increasingly strict. By using water instead of a hydraulic mineral oil in power-control hydraulic systems we can make a very positive step in complying with these regulations. However, introducing the water instead of oil in power control hydraulics is rather novel and difficult task. Moreover, due to several specifics of water that are also discussed in this paper, several requirements need to be fulfilled in every test rig and test specimen. In this paper we present a newly developed hydraulic test rig that is designed for these specific requirements of water as the hydraulic fluid in power control hydraulics. For direct comparison with oil system, the test rig is designed as a twin system with two equivalent circuits: one for water and one for oil tests. Some interesting results on dynamic response of both systems are presented. They show significant differences between the water and oil hydraulics. With these experiments, the test rig proved the suitability for the research in this new area and showed a good control of the parameters measured.
Keywords: voda; mineralna olja; hidravlična olja; pogonsko-krmilna hidravlika; proporcionalna hidravlika